Air exchange rates and migration of VOCs in basements and residences. (20th January 2015) - Du, L.; Batterman, S.; Godwin, C.; Rowe, Z.; Chin, J.‐Y.
Abstract: Basements can influence indoor air quality by affecting air exchange rates (AERs) and by the presence of emission sources of volatile organic compounds (VOCs) and other pollutants. We characterized VOC levels, AERs, and interzonal flows between basements and occupied spaces in 74 residences in Detroit, Michigan. Flows were measured using a steady‐state multitracer system, and 7‐day VOC measurements were collected using passive samplers in both living areas and basements. A walk‐through survey/inspection was conducted in each residence. AERs in residences and basements averaged 0.51 and 1.52/h, respectively, and had strong and opposite seasonal trends, for example, AERs were highest in residences during the summer, and highest in basements during the winter. Airflows from basements to occupied spaces also varied seasonally. VOC concentration distributions were right‐skewed, for example, 90th percentile benzene, toluene, naphthalene, and limonene concentrations were 4.0, 19.1, 20.3, and 51.0 μ g/m 3, respectively; maximum concentrations were 54, 888, 1117, and 134 μ g/m 3 . Identified VOC sources in basements included solvents, household cleaners, air fresheners, smoking, and gasoline‐powered equipment. The number and type of potential VOC sources found in basements are significant and problematic, and may warrant advisories regarding the storage and use of potentially strong VOCs sources in basements.